Pilomatrixoma (calcifying epithelioma of Malherbe). - Decuypere, F.A.G.; Theunissen, P.; Straetmans, J. (European Journal of Pediatric Dermatology, 2014)
Pilomatrixoma or calcifying epithelioma of Malherbe, is a benign skin neoplasm that embryologically arises from hair follicle matrix cells. A case of pilomatrixoma was reported in a 5-year-old little girl and the diagnosis difficulties were underlined.